SURVEYING TERRESTRIAL FOREST CARBON STORAGE AND ECOSYSTEM BENEFITS IN NIGERIA - Bichi, Armaya’u H.; Ogbodo, John Agbo; Ugwu, Okwudili J. (FUDMA JOURNAL OF SCIENCES, 2025)
This review paper explores the potential of open-source remote sensing-based measurement techniques to improve forest data collection and support Reducing Emissions from Deforestation and Forest Degradation (REDD+) monitoring, reporting, and verification framework in Nigeria's terrestrial forests. This study conducts a systematic analysis of four key areas: tropical deforestation and forest degradation, uncertainty in national forest health data, high costs of remote sensing data, and limited adoption of open-source remote sensing tools for Forest Reference Level (FREL) development. The findings suggest that open-source remote sensing technologies can enhance forest data collection, reduce costs, and support sustainable forest management and REDD+ initiatives. The study recommends developing an integrated open-source remote sensing framework for incorporating terrestrial forest carbon storage and ecosystem benefits data into Nigeria's national forest information system. This research contributes to the development of effective forest monitoring systems and supports Nigeria's efforts to achieve sustainable forest management and climate change mitigation goals.
Keywords: Carbon Sequestration; Ecosystem Benefits; Nigeria; Systematic Review; Terrestrial Forest Carbon Storage